Erratum: Sandoval, C.M., Nieves, E., Angulo, V.M., Rosa, J.A. & Aldana, E. (2011) Morphology of the eggs of the genus Belminus (Hemiptera: Reduviidae: Triatominae) by optical and scanning elec-tron microscopy. Zootaxa, 2970, 33–40. - Sandoval, C. M.; Nieves, E.; Angulo, V. M.; Rosa, J. A.; Aldana, E. (Zootaxa, 2011)
(Erratum)